Albright's syndrome: review of the literature and case report. - Sposto, Maria Regina [UNESP]; Navarro, Cláudia Maria [UNESP]; Oliveira, Maria Rita Brancini de [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Ferreira, Benedito Antônio [UNESP] (Nihon University School of Dentistry, 1994)
Albright's syndrome is characterized by the presence of polyostotic fibrous dysplasia, endocrinopathies and brown spots on the skin. In the present article the authors describe a case occurring in a 20-year-old female patient, who is currently being followed radiographically after a mandibular bone biopsy.
Keywords: adult; Albright syndrome; case report; face asymmetry; female; follow up; frontal bone; human; hyperpigmentation; jaw disease; pathology; review; Adult; Case Report; Facial Asymmetry; Female; Fibrous Dysplasia, Polyostotic; Follow-Up Studies; Frontal Bone; Human; Hyperpigmentation; Mandibular Diseases